Organizational Citizenship Behavior, Leadership Style, Work Motivation And Effect on Employee Performance - Ika Pratiwi; Andi Hasryningsih Asfar; Icin Quraysin; Martinus Tukiran (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to determine the influence of organizational citizenship behaviour, leadership style and work motivation on employee performance, both partially and simultaneously. The research approach uses quantitative approaches. The data analysis technique used is the multiple linear analysis techniques. The results showed a significant influence between organizational citizenship behaviour and Performance. There is no significant influence between leadership styles on Performance. There is a significant influence between Motivation and Performance in Employees. There is a significant influence between organizational citizenship behaviour, Leadership style and Motivation on Performance in Civil Servants (PNS).